Occupational exposure to blood and body fluids among primary healthcare workers in Johannesburg health district: High rate of underreporting - Collins C.E. Mbah; Zuberu B. Elabor; Olufemi B. Omole (South African Family Practice)
Background: Healthcare workers (HCWs) are at risk of bloodborne infections from sharp instrument injuries and skin and mucous membrane exposures to contaminated blood and body fluids (BBF). While these have clinical and occupational health implications, little is known about BBF exposure and its reporting pattern in South African primary healthcare (PHC). The aim of this study was to determine the rate of BBF exposure, the extent of reporting and the reasons for not reporting among HCWs in PHC facilities in Johannesburg, South Africa.